Gestão do cuidado à criança e ao adolescente com doença crônica na estratégia saúde da família - Machado, Amanda Narciso (2018)
Introduction: Health care for children and adolescents with chronic illness in the Family Health Strategy needs to be developed from the perspective of integrality so the Healthcare management can happen. Objective: To explain the healthcare management to children and adolescents with chronic illness in the Family Health Strategy. Methodology: Qualitative research whose empirical data were collected from July 2017 to January 2018 through a semi-structured interview with eleven health professionals who work in the Family Health Strategy in a municipality of Paraiba. The data were interpreted using the discourse analysis of the French line. The study has been approved by the Committee of Ethics in Research, opinion nº 2,046,377, CAAE 66235917.3.0000.5188. Results: the healthcare management was emphasized by some health care actions extended as embracement, trust among health professional team and family/children/adolescents with chronic disease, bonding formation, and social support, and others that restrain the integrality due to the organization of work process and infrastructural problems. It has been explained the importance and value of the family as a participant in the process of delivering care and a member of the support network reaching aims of the family dimension. The weakness of the professional, systemic, organizational, and societal dimensions is the result of the lack of commitment in the follow-up of children/adolescents with chronic disease in the Family health Strategy territory. Besides, the bureaucratization of the Unified Health System, the lack of responsibility from health professionals in longitudinal care, the absence of counter-referral from specialized care, and nonformulation of public policies for this specific population are also weaknesses. Conclusion: the fragmentation of support network to children and adolescents with chronic illness compromises the healthcare management evidencing the importance of its dimension to extend the health care. Healthcare management is expected to contribute to reaching the centered care of children/adolescents with chronic illness and their families.